2016
DOI: 10.1176/appi.ps.201500247
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of SOAR: Implementation and Outcomes of an Effort to Improve Access to SSI and SSDI

Abstract: Clients achieved better application outcomes when practitioners provided application assistance by using concepts from SOAR. However, training alone was not sufficient for successful SOAR implementation. Careful systems planning and dedicated staff resources are critical for improved outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…A recent Cochrane review identified CPIC as the main rigorous study in the literature of added value of multi-sector coalitions to improve health of minority communities, thereby supporting our choice of focusing on CPIC clients and agencies to explore the concept of whole person care. 18 Moving forward, the larger literature on care coordination, 44,45 team-based models like ACT, 24,25 and quality improvement collaboratives 46,47 may provide conceptual models, multi-sector network structures, and management strategies that can support the development of best practices for integration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent Cochrane review identified CPIC as the main rigorous study in the literature of added value of multi-sector coalitions to improve health of minority communities, thereby supporting our choice of focusing on CPIC clients and agencies to explore the concept of whole person care. 18 Moving forward, the larger literature on care coordination, 44,45 team-based models like ACT, 24,25 and quality improvement collaboratives 46,47 may provide conceptual models, multi-sector network structures, and management strategies that can support the development of best practices for integration.…”
Section: Resultsmentioning
confidence: 99%
“…22,23 Community-based multisector partnerships call for identifying and addressing health care needs in non-health care settings, such as churches, where care coordination could be challenging. 24 Although emerging multi-sector approaches, like SAMHSA's Recovery Support Strategic Initiative, use technical assistance to facilitate multi-sector collaboration, 25 we have a rudimentary understanding of the potential for intentional multi-sector, community-based collaborations to address physical health, mental health, and social needs of depressed individuals, especially in under-resourced minority communities that struggle to address health care disparities. 18,26 The Community Partners in Care (CPIC) study is a cluster-randomized controlled trial of depression quality improvement (QI) programs in minority, under-resourced communities in Los Angeles.…”
Section: Stakeholder Prioritiesmentioning
confidence: 99%
“…Despite significant resources dedicated to the in-person training model, an external evaluation of SOAR found that only 13% of trainees who received the in-person training were actually assisting with applications post-training ( 13 ). This corresponds with other research documenting that in-person trainings result in lower student performance compared with online training ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Over 50,000 SOAR-assisted applications have been processed, with a 65% approval rate (7). A recent investigation found SOAR-assisted applications were twice as likely as non-SOAR-assisted applications to be approved (6). However, that study did not examine the characteristics of SOAR applicants or applications that were associated with disability application outcomes.…”
mentioning
confidence: 96%
“…The Substance Abuse and Mental Health Services Administration (SAMHSA) developed the SSI/SSDI Outreach, Access, and Recovery (SOAR) program to increase access to disability benefits for homeless adults by training case managers about the process for determining disability (5,6). SOAR emphasizes five critical components for completing disability benefits applications: formal representation of the client by the case manager, submission of medical records, completion of a medical summary report to synthesize medical evidence, cosignature of a physician or psychiatrist on the medical summary report, and quality review of applications by a SOAR supervisor.…”
mentioning
confidence: 99%